ANALISA STRUKTUR MIKRO LAPISAN KROM DAN NIKEL PADA BAHAN DASAR KUNINGAN - Asfarizal Saad; Dadang Eka Juanda (Jurnal Teknik Mesin, 2015)
Chrome elektroplating in metal product is a way to increase the value of metal industial doer especially home industry. The best elektroplating can be shown in adhesion stratum in the metal, stratum shine, stratum thick, and substance of the stratum. Chrome elektroplating in a basic metal was done by two steps. First, nickel elektroplating and second, chrome elektroplating. Nickel elektroplating was done in current 3.5 Ampere, 9 Ampere, and 11 Ampere in twenty minutes. Both nickel and chrome elektroplating was done by dip method and current source from battery. Based on experimental data and the discussion, it can be perpoker substance, the thick of chrome elektroplating is 1 μm, 1.5 μm, 2.3 μm for current application 7 Ampere, 9 Ampere, and 11 Ampere solution. Coating adhesion and shiny of metal is good.